Analysis of the transcriptional unit encoding the genes for rubredoxin (rub) and a putative rubredoxin oxidoreductase (rbo) in Desulfovibrio vulgaris Hildenborough. - Brumlik, M J (1989)
The nucleotide sequence of a 2.0-kilobase-pair EcoRI restriction fragment upstream from the gene (rub, 162 base pairs) encoding rubredoxin from Desulfovibrio vulgaris Hildenborough indicates that it is part of a larger transcriptional unit, containing an additional 378-base-pair open reading frame which terminates 16 nucleotides from the translational start of the rub gene and could encode a polypeptide of 14 kilodaltons (kDa). Northern (RNA) blotting of RNA isolated from both D. vulgaris Hildenborough and Escherichia coli TG2 transformed with plasmid pJK29, which contains both genes on a 1.1-kilobase-pair SalI insert, confirms that the genes for this 14-kDa polypeptide and rubredoxin are present on a single transcript of 680 nucleotides. Strong evidence that the 14-kDa polypeptide is also a redox protein is provided by the fact that its NH2 terminus is homologous to desulforedoxin, which has been isolated from D. gigas as a small dimeric redox protein (36 amino acids per monomer), coordinating two iron atoms. Since rubredoxin is a potential redox partner for the 14-kDa protein, it has been tentatively named rubredoxin oxidoreductase, produced by the rbo gene. Southern blotting indicates that the rbo-rub operon is present in several species and strains of sulfate-reducing bacteria.